Congenital Portosystemic Shunt: An Under-Recognized Cause of Pulmonary Arterial Hypertension - Gopinath Periaswamy; Pudhiavan A; Navya Christopher; Kartheek Guthikonda; Venkatesh Kasi; Mathew Cherian (Asian Journal of Medical Radiological Research, 2022)
Background: Congenital portosystemic shunt (CPSS) is an uncommon vascular malformation which causes partial or complete shunting of the portal blood into systemic circulation. The purpose of this study is to retrospectively analyze the clinical features, imaging features and therapeutic outcomes of the cases of CPSS diagnosed in our institution. Subjects and Methods: A retrospective analysis of the clinical features, imaging features and therapeutic outcomes of all 8 patients of CPSS in our institution between 2017 and 2021 was conducted in this study. Park et al classification was used for intrahepatic portosystemic shunts and Morgan & Superina classification for extrahepatic portosystemic shunts. Results: Of the total eight cases of congenital portosystemic shunts, four cases had extrahepatic portosystemic shunts and four cases had intrahepatic portosystemic shunts. Five cases presented with pulmonary arterial hypertension (PAH).  Associated features were present in four cases among which two cases had PDA with ASD (Fig 4), one case had only PDA and one case had pulmonary arterio venous fistula, double SVC and focal nodular hyperplasia in the liver. However, no statistical correlation was found between the type of shunt or associated features with portosystemic shunts and development of PAH. Conclusion: In our retrospective study we observed that unexplained pulmonary arterial hypertension was present in the majority of cases of CPSS and the development of PAH could not be explained by the presence of associated conditions with it. CPSS could be a more common cause of undiagnosed PAH in children than previously recognised. Hence, the children with unexplained PAH should be screened for CPSS also.